Utilizing Life-Cycle Assessments of Two Chairs for the Design of an Eco-label to Influence Consumer Preferences. - Owen, Alexandria. (2017)
Abstract: The practice of sustainable design continues to grow in popularity, yet there are many roadblocks in place for average consumers interested in purchasing responsibly. It can be difficult to understand the meaning of labels, sort through the vast (and growing) number of them, or have confidence in the arbitrariness of their criteria. A Life Cycle Assessment, the most comprehensive method of evaluating any product or process, was performed on two different chairs. The results were used to develop sustainability criteria based on the "environmental cost" and "human health cost" of each chair, and an eco-label was designed for each chair according to their results. A usability study was designed with this eco-label, and with the feedback of over 100 participants, insights into consumer preferences were studied. It was successfully determined that a chair, when being shown with a "green" eco-label, was three times more preferred than when shown by itself.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Anil Saigal.; Committee: Daniel Hannon, and Stephen Levine.; Keyword: Sustainability.